Radiation therapy alleviates Doege–Potter syndrome accompanied with severe aortic valve insufficiency: a case report and literature review - Peng, Guiliang; Sun, Rongwan; Lei, Xiaotian; Deng, Chunni; Leng, Weiling; Zhang, Xing; Wu, Youli; Xie, Laiping; Hong, Pian; Long, Min; Chen, Liu (Frontiers in Oncology, 2025)
BackgroundDoege–Potter syndrome (DPS) is a rare paraneoplastic condition characterized by hypoglycemia resulting from the excessive secretion of insulin-like growth factor-2 (IGF-2) by a solitary fibrous tumor (SFT). This report presents an elderly patient with DPS complicated by severe cardiac conduction abnormalities, illustrating the clinical manifestation, therapeutic intervention, and multidisciplinary management strategy.Case presentationA 78-year-old woman was diagnosed with DPS, presenting with loss of consciousness with a blood glucose level of 1.41 mmol/L, and hypoglycemia was resolved with intravenous glucose. The initial laboratory investigation revealed elevated insulin levels of 7.17 μIU/mL, with suppressed C-peptide levels of 0.09 ng/mL and insulin-like growth factor-1 (IGF-1) levels of 26.47 ng/mL. Thoracic computed tomography (CT) identified a 13.6 cm × 8.6 cm mass in the right lower thoracic cavity. CT-guided transthoracic biopsy confirmed SFT with immunohistochemical positivity for CD34 and STAT6. Electrocardiogram (ECG) demonstrated frequent atrial premature complexes (29,292/24 hours), short runs of atrial tachycardia (144/24 hours), and paroxysmal ventricular premature complexes. Echocardiography revealed severe aortic valve insufficiency. Following multidisciplinary team (MDT) consultation, the surgically ineligible patient received tumor-directed radiotherapy (60 Gy in 30 fractions), glucocorticoid replacement (hydrocortisone 40 mg daily), and overnight carbohydrate supplementation to alleviate hypoglycemia. At 18-month follow-up, serial chest CT showed tumor size reduction. Holter monitoring revealed a substantial reduction in atrial premature complexes (1,955/24 hours vs. baseline 29,292/24 hours). The patient exhibited no recurrence of hypoglycemic episodes.ConclusionThis report describes a case of DPS with refractory hypoglycemia complicated by severe cardiac structural and conduction abnormalities. Radiotherapy combined with endocrine intervention effectively controlled tumor-associated hypoglycemia in this surgically ineligible patient.